Gross Motor Skills Are Associated with Symptoms of Attention Deficit Hyperactivity Disorder in School-Aged Children - Cristiana D'Anna; Fabio Carlevaro; Francesca Magno; Roberto Vagnetti; Pierpaolo Limone; Daniele Magistro (MDPI AG, 2024)
Attention deficit hyperactivity disorder (ADHD) is among the most prevalent disorders in children and is frequently linked with motor difficulties that can impact both daily motor tasks and overall developmental trajectories. The objective of this study was to analyse the association between gross motor skills and ADHD symptoms. Using a cross-sectional research design, data were collected from a sample of primary school children (N = 2677; mean age = 8.58 years, SD = 1.49 years). The Gross Motor Development-3 Test (TGMD-3) was employed to assess participants' gross motor skills, whereas the ADHD Rating Scale (SDAI), completed by teachers, evaluated ADHD symptoms through two subscales: inattention and impulsivity/hyperactivity. The results revealed an association between motor development and ADHD symptoms, with greater proficiency in gross motor skills correlating with lower symptoms reported on the SDAI. Logistic regression analyses indicated that the TGMD-3 was significantly associated with the risk of ADHD in matched samples of at-risk children and controls. The evaluation of gross motor development proves to be a useful tool for monitoring global development, paying attention to any critical issues, particularly in relation to the variables of inattention and hyperactivity.